Genomics-informed elucidation of trait-phenotype relationships and MABB approaches deliver major gene blast resistance in the aromatic rice landrace Mushk Budji - Shikari, Asif Bashir; Khan, Raheel Shafeeq; Ain, Noor-ul; Mohiddin, F. A.; Khan, Gazala Hassan; Sofi, Najeeb-ul-Rehman; Dar, Zahoor A.; Ahangar, M. Ashraf; Ali, Gowhar; Wani, Aflaq Hamid; Padder, Bilal A. (Frontiers in Genetics, 2026)
IntroductionA novel set of pyramided lines for durable blast resistance was developed using marker-assisted backcross breeding (MABB) strategy in the genetic background of the aromatic landrace Mushk Budji (MB).MethodsSimultaneous-but-stepwise transfer of the blast resistance genes Pi54 and Pi9 was achieved through the integration of foreground selection (FS) and background genome recovery processes, aided by genome-wide SSR and >1500 KASP markers. MABB, whole genome re-sequencing, coupled with stringent phenotypic selection for aroma, amylose content, kernel dimensions, and cooking quality, helped minimize the linkage drag and achieve early recurrent parent genome (RPG) recovery in the inter-cross BC2F2:3 generation.ResultsThe two-gene lines carrying Pi9 + Pi54 were developed through inter-crossing corresponding near-isogenic lines (NILs) with an RPG of approximately 90%. With the help of sequencing of the derived NILs, we were able, for the first time, to establish the role of major alleles underlying rice quality and stress resilience in MB. In the process, we confirmed the retention of favorable alleles at key genetic loci, such as BADH2 (aroma), Wx (amylose content), Rc (white pericarp), Hd1/Hd4/Hd5 (heading date), and COLD1/COLD6 (cold tolerance) in the derived NILs. GGE biplot analysis revealed stable performance of five advanced lines across target ecologies.DiscussionThe set of NILs was useful in elucidating the phenotypic effects of 11 genes related to grain type, quality, and adaptability traits in the landrace MB. Multi-environment screening for blast resistance, at hot spot locations, in addition to artificial inoculation, validated the resistance response of the lines to both leaf and neck blast. This study demonstrates the successful integration of genomics-assisted breeding and phenotypic selection to improve a heritage rice variety for enhanced disease resistance and ecological adaptation. The development of improved MB lines represents a rare endeavor towards the area expansion and conservation of the heirloom rice.